Capillary length in a fluid-fluid demixed colloid-polymer mixture. - Aarts, D (2005)
We report measurements of the interfacial profile close to a vertical wall in a fluid-fluid demixed colloid-polymer mixture. The profile is measured by means of laser scanning confocal microscopy. It is accurately described by the interplay between the Laplace and hydrostatic pressure and from this description the capillary length is obtained. For different statepoints approaching the critical point the capillary length varies from 50 to 5 microm. These results are compared to theory. The mass density difference Deltarho is calculated from the bulk phase behavior, which is described within free volume theory with polymers modeled as penetrable hard spheres. The interfacial tension gamma is calculated within a squared gradient approximation. The capillary length is then given through with g equal to the Earth's acceleration. Predictions from theory are in overall qualitative agreement with experiment without the use of any adjustable parameter.